Agency and the Critical Study of Religion - Meyer, Gaelin M. (Journal for the study of religion, 2022)
The critical study of religion is enchanted by modern problematics, and this limits the feasibility of the project. Both secularity and modernity have been deconstructed in recent decades, but the primacy of the modern and secular agentic human remains largely unchallenged. Tracing this trend back in European history shows that a definitive collapsing of agency was necessary for the development of modern political and social structures. Modern prescriptions on agency limit the study of religion - a domain which is largely constituted by narratives involving non-human agents. A remedy for the impasse may be found in looking to a nonmodern conceptual apparatus for new avenues in theory-making and applying these concepts to the critical study of religion in the 21st century.